2004
DOI: 10.1002/pbc.20124
|View full text |Cite
|
Sign up to set email alerts
|

Wnt/Frizzled signaling in Ewing sarcoma

Abstract: These results provide evidence that components of Wnt/Fz pathway are expressed and an intact Wnt/Frizzled signaling pathway exists in ESFT cell lines. Activation of the Wnt pathway in ESFT suggests that Wnt modulates cell motility rather than cell proliferation. Hence, activation of this pathway may influence metastatic potential of ESFT.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
50
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 69 publications
(54 citation statements)
references
References 39 publications
4
50
0
Order By: Relevance
“…Earlier we observed that Wnt-3a CM induced the formation of long cytoplasmic extensions in TC-32 cells, an ESFT cell line (38). In the current study, we reproduced these results with purified recombinant Wnt-3a and further characterized the morphological changes.…”
Section: Resultssupporting
confidence: 83%
“…Earlier we observed that Wnt-3a CM induced the formation of long cytoplasmic extensions in TC-32 cells, an ESFT cell line (38). In the current study, we reproduced these results with purified recombinant Wnt-3a and further characterized the morphological changes.…”
Section: Resultssupporting
confidence: 83%
“…The mouse cells were grown on TripleFlasks (Fisher Scientific, Newark, DE, USA) with 500 cm 2 culture area until they were 80% confluent, and then the medium was changed to 100 ml serum-free DMEM. Two successive 72-h harvests of conditioned medium were collected and pooled (Uren et al 2004, Chen et al 2008. Typically, CM was stored at K80 8C; once thawed, medium was kept refrigerated and retained activity for several weeks.…”
Section: Reagentsmentioning
confidence: 99%
“…Immunofluorescence was performed on C18-4 cells using phalloidin-FITC for actin filament staining. The number of extensions longer than the cell body was counted for each condition and represented in a graph (Uren et al 2004). Human germ cells cultured in the presence and absence of WNT3A CM were analyzed every day and the number of colonies in each well was counted using an inverted microscope.…”
Section: Morphological Analysismentioning
confidence: 99%
“…It can act as either an agonist or antagonist of WNT/β-catenin signaling, depending on the cellular context and the presence of the co-factor Kremen 2 [12][13][14]. In ES Kremen 2 is absent and DKK2 stimulates canonical β-catenin signaling.…”
Section: Introductionmentioning
confidence: 99%